2013
DOI: 10.1073/pnas.1305961110
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mutual antagonism between hypoxia-inducible factors 1α and 2α regulates oxygen sensing and cardio-respiratory homeostasis

Abstract: Breathing and blood pressure are under constant homeostatic regulation to maintain optimal oxygen delivery to the tissues. Chemosensory reflexes initiated by the carotid body and catecholamine secretion from the adrenal medulla are the principal mechanisms for maintaining respiratory and cardiovascular homeostasis; however, the underlying molecular mechanisms are not known. Here, we report that balanced activity of hypoxia-inducible factor-1 (HIF-1) and HIF-2 is critical for oxygen sensing by the carotid body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 34 publications
2
102
3
Order By: Relevance
“…Previous workers have shown that HIF1α is found ubiquitously in vivo whereas HIF2α is tissue specific and is upregulated in specific cells of different organs [25,7]. However, both the isoforms of HIFα are expressed within the CB and are already considered as the master regulators of O 2 homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous workers have shown that HIF1α is found ubiquitously in vivo whereas HIF2α is tissue specific and is upregulated in specific cells of different organs [25,7]. However, both the isoforms of HIFα are expressed within the CB and are already considered as the master regulators of O 2 homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the isoforms of HIFα are expressed within the CB and are already considered as the master regulators of O 2 homeostasis. Chronic hypoxia activates both HIF1α and HIF2α [26] and has various maladaptive effects on CB structure and function [10,6,7]. Several clinical manifestations of sustained hypoxia can be seen in patients of chronic mountain sickness, chronic obstructive pulmonary disease (COPD), cerebral ischemia, pulmonary arterial hypertension, etc in which HIFs play a vital role [27,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations